Wild zebra finches are attracted towards acoustic cues from conspecific social groups. (5th March 2022) - Adrian, Corinna; Griffith, Simon C; Naguib, Marc; Schuett, Wiebke
Abstract: Social information gathered by observing others often supplements personal information collected from direct interactions with the physical environment during decision-making. Social information use may be particularly beneficial in harsh environments or if resources are distributed patchily, ephemeral, and unpredictable, and hence difficult to locate. We experimentally tested the use of acoustic cues in wild zebra finches ( Taeniopygia guttata ) as they flew around their arid habitat as a way of locating conspecifics on the ground, and potentially accessing useful social information. Joining a conspecific group may reduce the predation risk, and if they are foraging may also improve foraging efficiency, as the distribution of zebra finch food (grass seed) is scattered and unpredictable in their natural habitat, the Australian arid zone. We conducted playback experiments along vegetated creek lines radiating out from an artificial dam where all birds in the population were coming for drinking water. We broadcast recordings of vocalizations from foraging conspecific groups to birds using these creek lines to move to or from the water into the wider habitat. Zebra finches were more likely to land near the loudspeaker when conspecific vocalizations were broadcast compared to white noise. Birds flying low and close to the loudspeaker were most likely to land. Our results indicate that zebra finches use acoustic cues of conspecifics as a source of social information for grouping decisions. Use of such information may also enhance foraging efficiency in environments with unpredictable and scarce foraging locations, and reduce predation risk for calling and responding individuals. Abstract : Social information gathered by observing others may often be highly beneficial in harsh environments. We conducted playback experiments to assess the use of social information for locating conspecifics in wild zebra finches. Zebra finches were more likely to land when vocalizations from foraging zebra finches were broadcast compared to white noise. Use of such social information may enhance foraging efficiency in environments with scarce foraging locations and may reduce predation risk.